Ferroptosis: A Trigger of Proinflammatory State Progression to Immunogenicity in Necroinflammatory Disease - Li, Jing-yan; Yao, Yong-ming; Tian, Ying-ping (Frontiers in Immunology, 2021)
Ferroptosis is a novel and programmed form of necrotic-like cell death, characterized by physiopathologies of lipid peroxidation, and induced by iron overloading and cysteine, which is notably presented in cancer, neurodegeneration, immune disease, inflammatory disease, and ischemia/reperfusion injury. Ferroptosis is triggered by overload reactive oxygen species (ROS) and imbalance of redox reaction, which is generated by reduced glutathione synthesis and activity of enzyme glutathione peroxidase 4 (GPX4). Recently, it is revealed that programmed necrosis of pyroptosis, necroptosis, and ferroptosis is inherently more immunogenic than apoptosis, and leads to the releases of inflammatory cytokines which is generally defined as Danger-Associated Molecular Patterns (DAMP), resulting in a necroinflammatory response, which can drive the proinflammatory state under certain biological circumstances. Ferroptosis is regarded as a potential therapeutic and molecular target for the treatment of necroinflammatory diseases, and futher investigation into the underlying pathophysiological characteristics and molecular mechanisms may lay a theoretical foundation for an interventional strategy. The highlight of this review focus on the essential roles and central regulatory mechanisms of ferroptosis in the development of necroinflammatory associated diseases and its potential as a therapeutic target for diseases.